Clinical efficacy and safety outcomes of bempedoic acid for LDL-C lowering therapy in patients at high cardiovascular risk: a systematic review and meta-analysis. (14th October 2021) - Lin, Y; Parco, C; Karathanos, A; Krieger, T; Schulze, V; Chernyak, N; Icks, A; Kelm, M; Brockmeyer, M; Wolff, G
Abstract: Background: Bempedoic acid (BA) is a novel oral low-density lipoprotein cholestrol (LDL-C) lowering drug. Its efficacy and safety for clinical outcomes in high cardiovascular risk patients remains unknown. Objectives and methods: A systematic review was performed and randomized controlled trials (RCTs) of BA vs. placebo in high cardiovascular risk patients reporting clinical efficacy and safety outcomes were included in a meta-analysis. Cumulative odds ratios (OR) and mean differences with 95% confidence intervals (CI) were reported as summary statistics. Results: Six RCTs with a total of 3, 956 patients and follow-ups of four to 52 weeks were identified. There was no difference in MACE (OR 0.84; CI 0.61, 1.15), all-cause mortality (OR 2.37; CI 0.80, 6.99) and cardiovascular mortality (OR 1.66; CI 0.45, 6.04) for BA vs. placebo. BA showed beneficial trends for nonfatal myocardial infarction (OR 0.57; CI 0.32, 1.00) and was associated with a lower risk of new-onset or worsening of diabetes mellitus (OR 0.68; CI 0.49, 0.94) and non-coronary revascularization (OR 0.41; CI 0.18, 0.95), but higher risk of gout (OR 3.29; CI 1.28, 8.46) and a trend for worsening of renal function (OR 4.24; CI 0.98, 18.39) and muscular disorders (OR 2.60; CI 1.15, 5.91). Conclusion: Bempedoic acid in high cardiovascular risk patients showed no significant effects on major cardiovascular outcomes in short-term follow-up. Unfavourable effects on muscular disorders, renal function and the incidence of gout sound a note of caution. Hence, further studies with longer-term follow-up are needed to clarify the risk/benefit ratio of this novel therapy. Funding Acknowledgement: Type of funding sources: None.